2015
DOI: 10.1097/scs.0000000000001941
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomeningocele With Orbital Extension as a Complication of Fronto-Orbital Advancement and Remodeling in Craniosynostosis

Abstract: Pseudomeningocele has not previously been described in FOAR, but in a large series of consecutive patients, we have identified a 2.5% incidence. This incidence increases to 10% in the syndromic population of patients undergoing FOAR. The risk factors include a diagnosis of syndromic craniosynostosis, dural tear, hydrocephalus or raised ICP, infection, persistent cerebrospinal fluid (CSF) leak, or presence of dead space. Preventative strategies include CSF management before or post-FOAR. The ultimate treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A report indicated that a higher infection rate was observed in patients with operative time longer than 4 hours than in patients with shorter operative time. The infection risk in patients receiving external ventricular drainage was 9.4 times higher than in patients without it (23). Due to the disruption of the blood-brain barrier in craniotomy patients, the immune function of their central nervous system was reduced longterm, and placement of a drainage tube increased infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…A report indicated that a higher infection rate was observed in patients with operative time longer than 4 hours than in patients with shorter operative time. The infection risk in patients receiving external ventricular drainage was 9.4 times higher than in patients without it (23). Due to the disruption of the blood-brain barrier in craniotomy patients, the immune function of their central nervous system was reduced longterm, and placement of a drainage tube increased infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other possible risk factors for PM formation include a prior diagnosis of syndromic craniosynostosis, a persistent CSF leak, the presence of a bony fracture or bony defect, or the presence of dead space. 3 Possible risk factors in our patient included the presence of a bony defect and the presence of dead space.…”
Section: Article In Pressmentioning
confidence: 98%
“…1,2 Clinical symptoms usually arise when there is mass effect on the surrounding structures. 3 There are very few reports of orbital PMs in the current literature. 1,4 Here, we report a case of a 17-year-old male status-post gross tumor resection of a pilocytic astrocytoma, who presented with a PM involving the right optic canal and superior orbit and was treated via an anterior orbitotomy.…”
mentioning
confidence: 99%